Peran Aksi Kolektif untuk Mitigasi Bencana dalam Resiliensi Komunitas Menghadapi Tanah Longsor - Lubis, Indri Wardiah Abriana; Pandjaitan, Nurmala Katrina (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2024)
Landslide disasters cause various impacts such as damage to facilities and infrastructure, loss of housing, too many casualties as well as providing psychological impacts that affect the social life of the community. The negative impact of disasters can be reduced by mitigating so that communities can survive. Muara 1 Village, Cibunian Village has carried out mitigation activities both structural and non-structural. Collective action by communities can achieve resilience if communities take collective action. The research method uses a quantitative approach through questionnaires and a qualitative approach with in-depth observation and interviews. Respondents in this study amounted to 80 respondents. Quantitative data was processed using Microsoft Excel 365 application and IBM SPSS Statistic 24 application. This study uses simple statistical analysis supported by qualitative data to see collective action variables with community resilience in facing landslide disasters. The results showed that collective action is still top down and not yet fully the community of Kampung Muara 1 is said to be resilient.